2006
DOI: 10.1002/jor.20280
|View full text |Cite
|
Sign up to set email alerts
|

Repair of peripheral nerve defect with direct gradual lengthening of the proximal nerve stump in rats

Abstract: ABSTRACT:We investigated the effect of direct gradual lengthening on the proximal nerve stump and subsequent nerve regeneration in rats. A 10-mm-long nerve segment was resected from the sciatic nerve of each rat. The proximal nerve stump was directly lengthened at a rate of 1 mm/day using an original external nerve distraction device. Experiment I: After distraction periods of 10, 15, and 20 days, the length of each nerve was evaluated, and the lengthened nerve stump was also examined by immunohistochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…6,8,9 In addition to this, our previous study also showed that nerve regeneration after repair of a segmental nerve defect by gradual lengthening of the proximal nerve stump was as good as that of autologous nerve grafting. 6 Thus, primary nerve lengthening might have potential application in the repair of peripheral nerve defects. However, little is known about the effect of direct gradual stretching on the nerve stump.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…6,8,9 In addition to this, our previous study also showed that nerve regeneration after repair of a segmental nerve defect by gradual lengthening of the proximal nerve stump was as good as that of autologous nerve grafting. 6 Thus, primary nerve lengthening might have potential application in the repair of peripheral nerve defects. However, little is known about the effect of direct gradual stretching on the nerve stump.…”
Section: Discussionmentioning
confidence: 66%
“…As described in our previous study, nerve lengthening was achieved via the stretching of the ring. 6 The stretching was performed at the same time daily while the rats were under sodium pentobarbital (20 mg/kg i.p.) anesthesia.…”
Section: Surgical Procedures and Nerve Lengtheningmentioning
confidence: 99%
See 2 more Smart Citations
“…There is much research being conducted to overcome these issues, and we also have developed a nervelengthening method as a new strategy for repair of a segmental peripheral nerve defect. [3][4][5] This method involves grasping both nerve stumps and attaching traction sutures to an external fixator, then using the external fixator to gradually stretch both nerve stumps simultaneously to the point where they can be sutured together. With this nerve-lengthening method, there is only one anastomosis site, a low incidence of nerve stump shape/diameter mismatch, and no interposition of avascular tissue.…”
mentioning
confidence: 99%